Respon Pertumbuhan Dan Produksi Kacang Tanah (Arachis Hypogaea L.) Terhadap Pemberian Pupuk Kandang Kambing Dan Pupuk Organik Cair Bonggol Pisang - Aris Agus Wahyudi; Maimunah Maimunah; Erwin Pane (Universitas Medan Area, 2019)
The study aimed to determine the response of growth and production of peanuts to the provision of goat manure and banana hump liquid organic fertilizer. This study used a Randomized Block Design (RBD) with 3 replications. Factorial consisting of II treatment factors, Factor I treatment of giving goat manure and Factor II, the treatment of Hump Banana POC treatment The parameters observed in this study; Plant height (cm), number of branches (branches), number of pods per sample (fruit), wet weight of production per sample (g), wet weight of production per plot (g), production dry weight per sample (g), and dry weight Production Per Plot (g). The results showed that goat manure had an effect on growth but did not affect the production of peanut plants, liquid organic fertilizer of banana humps had an influence on the growth and production of peanut plants, Combination of goat manure and banana hump liquid organic fertilizer had no significant effect on growth and production of peanut plants.